Preparation of palladium supported carbon-based catalyst and its application in suzuki coupling reaction
Patent Information
- Application Number
- CN202610976174.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0011]鉴于此,本发明提出了一种钯负载型碳基催化剂的制备及其在Suzuki偶联反应中的应用,旨在解决当前技术中钯催化剂分离回收困难、钯残留污染严重,现有多相钯催化剂制备繁琐、成本高、活性与稳定性难以兼顾及工业化放大困难的问题
1)本发明的钯负载型碳基催化剂采用固相研磨结合低温煅烧一步法制备,无需有机溶剂和有毒配体,仅需简单工艺即可完成。载体β-环糊精和三聚氰胺廉价易得,钯负载量远低于现有多数催化剂的负载量,生产成本低。
Smart Images

Figure CN122999180A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic synthesis technology, and more specifically, to the preparation of a palladium-supported carbon-based catalyst and its application in the Suzuki coupling reaction. Background Technology
[0002] C-carbon coupling reactions are among the most fundamental and widely used reactions in organic synthetic chemistry for constructing carbon-carbon bonds. Their development has directly driven technological advancements in multiple fields, including pharmaceuticals, pesticides, polymer materials, fine chemical intermediates, and electronic information materials. Among these, the Suzuki-Miyaura coupling reaction (Suzuki coupling reaction for short) has become the preferred method for synthesizing biphenyl compounds due to its significant advantages, such as mild reaction conditions, excellent functional group tolerance, non-toxic and easily separable byproducts, and stable and readily available organoboron reagents. It is widely used in the industrial production of sartan antihypertensive drugs, nonsteroidal anti-inflammatory drugs, antitumor drugs, and liquid crystal materials.
[0003] Currently, the industrial production of Suzuki coupling reactions still primarily relies on homogeneous palladium catalysts, such as tetra(triphenylphosphine)palladium, palladium acetate, and dichlorobis(triphenylphosphine)palladium. While these homogeneous catalysts exhibit high catalytic activity and good selectivity, they suffer from a series of inherent drawbacks: First, the catalyst is completely miscible with the reaction system, requiring complex separation processes such as column chromatography and recrystallization after the reaction, and is almost impossible to reuse, resulting in high production costs and extremely low utilization of the precious metal palladium. Second, palladium metal tends to remain in the product as a complex after the reaction. For fields with strict requirements on heavy metal content, such as pharmaceuticals and food contact materials, an additional expensive palladium removal process is required, significantly increasing production costs and environmental pressure. Third, most homogeneous catalysts require the use of organophosphine ligands such as triphenylphosphine, which are not only expensive and highly toxic but also easily oxidized and deactivated in air, increasing operational difficulty and environmental risks. Fourth, some homogeneous catalytic systems require high-boiling-point toxic organic solvents such as toluene and DMF, resulting in high waste treatment costs and contradicting the development concept of green chemistry.
[0004] To address the aforementioned drawbacks of homogeneous palladium catalysts, researchers over the past two decades have shifted their focus to the development of heterogeneous palladium catalysts. This involves loading palladium nanoparticles onto various solid supports, enabling easy separation and reusability of the catalysts. Currently reported support materials mainly include carbon-based materials (graphene oxide, carbon nanotubes, activated carbon), inorganic oxides (silicon dioxide, aluminum oxide, cerium dioxide), magnetic nanoparticles (ferric oxide), natural polymers (chitosan, cellulose), and organic porous materials (covalent organic frameworks (COFs), metal-organic frameworks (MOFs). While various heterogeneous catalysts have solved the separation and recovery problems to some extent, many technical challenges remain to be addressed. In 2019, Babak Jaleh's group prepared a stainless steel mesh-GO@Pd catalyst using liquid laser ablation. This catalyst achieved a 97% biphenyl yield after 1.5 hours of reaction at 90°C and could be recycled up to 5 times. However, this method requires expensive laser ablation equipment, resulting in high investment costs. Furthermore, the catalyst loading is difficult to control precisely, hindering large-scale production. Additionally, the catalyst dosage is as high as 70 mg / mmol substrate, far exceeding the economic threshold for industrial applications. In the same year, Mohammad Yousefi's group first prepared a PdNPs / RGO catalyst by reducing and modifying graphene oxide with sandalwood extract. This catalyst achieved a 95% yield after 2 hours of reaction in an aqueous phase at 50°C and could be recycled up to 8 times. However, this method relies on natural plant extracts, the composition of which is greatly affected by origin, season, and extraction process, leading to poor batch stability and failing to meet the consistency requirements for industrial production.
[0005] In 2020, M. Samy El-Shall's research group developed a partially functionalized reduced graphene oxide-supported palladium catalyst, achieving a conversion rate of 97.7% after 5 minutes of microwave-assisted reaction at 80°C. However, microwave reactions suffer from significant scale-up effects, making it difficult to reproduce the excellent performance in industrial batch reactors; furthermore, the catalyst has a palladium loading of up to 3 wt%, resulting in a large amount of precious metal and high cost. Around the same time, Kootak Hong et al. reported a chitosan-encapsulated Fe3O4 / SiO2-NH2 magnetic nanocatalyst. This catalyst achieved a 98% yield after 10 minutes of reaction at room temperature and could be rapidly recovered through magnetic separation, showing no significant decrease in activity after 10 reuses. However, the preparation process of this catalyst is extremely cumbersome, requiring five steps: co-precipitation of iron(III) oxide, tetraethyl orthosilicate coating of silica, silane coupling agent modification, o-phenylenediamine grafting, and in-situ reduction of palladium salts. Each step requires large amounts of organic solvents and chemical reagents, resulting in low atom utilization and large emissions of waste, contradicting the principles of green chemistry.
[0006] In 2021, Sreenath Reddy Aabaka et al. prepared a Pd@NC NPs catalyst using in-situ generated nanocellulose as a support. This catalyst achieved a 99% yield in 5 hours of reaction in an aqueous phase at room temperature and could be recycled 11 times. However, the preparation of nanocellulose requires complex pretreatment and enzymatic / acid hydrolysis processes, resulting in a long production cycle and high cost. Furthermore, the cellulose-based support is prone to swelling in the aqueous phase reaction, leading to poor structural stability over long-term use. Yuan Li et al. designed a (Pd / C)@TpPa COFs catalyst with an eggshell structure, utilizing the confinement effect of COFs to suppress the aggregation of palladium nanoparticles, and it can be recycled 5 times. However, the synthesis of covalent organic frameworks (COFs) requires high temperature and high pressure conditions, with a reaction cycle lasting several days, and the raw materials are expensive. Currently, only gram-scale preparation in the laboratory can be achieved, and there is still a huge gap between this and industrial application.
[0007] In 2022, Mansour Binandeh et al. prepared a magnetic composite catalyst coated on an amino linker. This catalyst achieved a 98% yield in an aqueous phase at 70°C for 30 minutes and exhibited an extremely high TOF value. However, this study only verified the catalyst's single-cycle activity and did not conduct cyclic stability experiments. Furthermore, the preparation process of the magnetic support was complex, and the grafting rate of the surface amino groups was difficult to control, resulting in significant fluctuations in catalyst performance.
[0008] In addition to the specific technical defects mentioned above, existing heterogeneous palladium catalysts also generally suffer from the following common problems: First, it is difficult to balance activity and stability. Highly active catalysts often have small palladium nanoparticles with high surface energy, making them prone to aggregation and leaching, resulting in poor cycle stability. On the other hand, catalysts with good stability usually have excessively strong palladium-support interactions, which reduce catalytic activity. Second, substrate universality is limited. Most catalysts only show high activity for iodoaromatics, with significantly reduced activity for bromoaromatics and almost no activity for chlorinatedaromatics. They also have poor tolerance to heterocyclic substrates and substrates containing sensitive functional groups. Third, they lack greenness. Most catalytic systems still require the use of organic solvents or the addition of surfactants. Some catalysts use toxic reducing agents such as hydrazine hydrate and sodium borohydride in their preparation process, which is not environmentally friendly.
[0009] Among carbon-based support materials, melamine, as a cheap and readily available nitrogen-rich carbon source, contains three amino groups and three triazine ring nitrogen atoms in its molecule, providing abundant coordination sites for palladium metal, effectively anchoring palladium nanoparticles and inhibiting their aggregation. However, melamine itself has low surface energy, small specific surface area, and lacks hydrophilic groups in its molecule, resulting in extremely poor hydrophilicity. In aqueous phase reactions, it is difficult to fully contact the substrate, leading to low mass transfer efficiency and poor catalytic activity. Cyclodextrin is a natural macrocyclic compound obtained from starch through enzymatic hydrolysis, possessing a unique barrel-shaped structure with a "hydrophilic outer cavity and hydrophobic inner cavity." The numerous hydroxyl groups in its outer cavity not only endow the catalyst with good hydrophilicity but also form coordination bonds with palladium metal; simultaneously, its hydrophobic inner cavity can encapsulate organic substrates, playing a role in phase transfer catalysis. However, when cyclodextrin is used alone as a support, it is prone to pyrolysis and structural collapse during calcination, failing to effectively stabilize palladium nanoparticles, resulting in poor catalyst cycle stability. Typically, the activity decreases significantly after three cycles.
[0010] In summary, no existing palladium-based heterogeneous catalyst can simultaneously meet all the requirements of simple preparation process, low cost, high catalytic activity, good stability, broad substrate versatility, environmental friendliness, and ease of industrial scale-up. Therefore, developing a novel palladium-supported carbon-based catalyst that can synergistically solve the above problems has extremely important theoretical significance and practical application value for promoting the green industrialization of the Suzuki coupling reaction. Summary of the Invention
[0011] In view of this, the present invention proposes a method for preparing a palladium-supported carbon-based catalyst and its application in the Suzuki coupling reaction, aiming to solve the problems of difficulty in separating and recovering palladium catalysts, serious palladium residue pollution, cumbersome preparation, high cost, difficulty in balancing activity and stability, and difficulty in industrial scale-up of existing heterogeneous palladium catalysts.
[0012] This invention proposes a method for preparing a palladium-supported carbon-based catalyst, characterized by comprising the following steps: S1: The carrier material and palladium chloride are mixed and then ground to obtain a mixture. S2: The mixture is heated and then calcined to obtain a palladium-supported carbon-based catalyst.
[0013] Preferably, the mass ratio of the carrier material to palladium chloride is 100:1.
[0014] Preferably, in the carrier material, the proportion of β-cyclodextrin (β-CD) is 20wt%~100wt%, and the proportion of melamine (Mela) is 0~80wt%.
[0015] Preferably, the carrier material contains 80 wt% β-cyclodextrin and 20 wt% melamine.
[0016] Preferably, the grinding is carried out in a ball mill at 50 Hz.
[0017] Preferably, the heating rate is 4~6℃ / min; the calcination is carried out under argon protection, the calcination temperature is 330~360℃, and the calcination time is 1~2h.
[0018] Another object of the present invention is to provide a palladium-supported carbon-based catalyst prepared by the method for preparing the palladium-supported carbon-based catalyst.
[0019] Another object of the present invention is to provide a method for preparing the palladium-supported carbon-based catalyst and its application in the Suzuki coupling reaction. The reaction for synthesizing the biphenyl compounds is as follows: a Suzuki coupling reaction is carried out by mixing the haloaromatic hydrocarbon of Formula I, the arylboronic acid compound of Formula II, the palladium-supported carbon-based catalyst, the solvent, and the base to obtain the biphenyl compound of Formula III. The reaction equation for the synthesis of the biphenyl compounds is as follows: , Wherein, R1 includes an aryl or substituted aryl group, wherein the substituents of the substituted aryl group include C1-C1. 10 Alkyl, C1-C 10 Alkoxy, halogenated C1-C 10 Alkyl, halogenated C1-C 10 Alkyl, halogen, cyano, nitro, acetyl, aldehyde, carboxyl, ester, or hydroxyl groups; X includes Br or I; R2 includes hydrogen, halogens, and C1-C. 10 Alkyl, C1-C 10 Alkoxy, halogenated C1-C 10 Alkyl, halogenated C1-C 10 Alkoxy; The addition ratio of the haloaromatic hydrocarbons shown in Formula I, the arylboronic acid compounds shown in Formula II, and the palladium-supported carbon-based catalyst is 1 mmol: 1.5 mmol: (5~10) mg; The addition ratio of the halogenated aromatic hydrocarbon, solvent and base shown in Formula I is 1 mmol: 1~2 mL: 2 mmol; The solvent includes ethanol, water, and a mixture of ethanol and water, wherein the volume ratio of ethanol to water in the mixture of ethanol and water is 1:1. The alkali includes potassium carbonate, sodium carbonate, potassium acetate, sodium acetate, potassium phosphate, sodium phosphate, triethylamine, cesium carbonate, sodium hydroxide, or potassium hydroxide; The reaction temperature for synthesizing the biphenyl compounds is 80~100℃, and the reaction time is 3~24h.
[0020] Preferably, R1 is phenyl, naphthyl, or a substituted phenyl group, wherein the substituents of the substituted phenyl group include C1-C4 alkyl, C1-C4 alkoxy, halogenated C1-C4 alkyl, halogen, acetyl, aldehyde, or hydroxyl.
[0021] Preferably, R2 includes hydrogen, halogen, C1-C4 alkyl, C1-C4 alkoxy, halogenated C1-C4 alkyl, and halogenated C1-C4 alkoxy.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) The palladium-supported carbon-based catalyst of this invention is prepared by a one-step method combining solid-phase grinding and low-temperature calcination, which requires no organic solvents or toxic ligands and can be completed with only simple processes. The supports β-cyclodextrin and melamine are inexpensive and readily available, and the palladium loading is much lower than that of most existing catalysts, resulting in low production costs.
[0023] 2) The β-CD@Pd catalyst prepared in the embodiments of the present invention for coupling iodobenzene and phenylboronic acid has a yield of up to 98%; the minimum catalyst dosage is only 5 mg / mmol of substrate, and a yield of 96% can be achieved by reacting at 90°C for 5 h, which is much faster than most existing catalysts.
[0024] 3) After the palladium-supported carbon-based catalyst of the present invention is recycled 7 times, the product yield still remains at 86%. The recycling experiment shows that the main functional group structure of the catalyst is stable, with only a small amount of surface palladium loss, which greatly reduces the catalyst consumption in industrial applications.
[0025] 4) The palladium-supported carbon-based catalyst of this invention can catalyze the coupling of iodoaromatics, bromoaromatics, and various substituted arylboronic acids, covering multiple functional groups such as alkyl, alkoxy, and halogen. Furthermore, it achieves high product yields, meeting the synthesis requirements of various biphenyl compounds.
[0026] 5) In a 20-fold scale-up experiment, the reaction yield using the palladium-supported carbon-based catalyst of this invention still reached 94%, which is basically consistent with the results of the small-scale test. The catalyst of this invention is easy to separate by simple filtration, leaves no heavy metal residue, and the product post-processing is simple, making it suitable for large-scale industrial production of biphenyl-based fine chemicals. Attached Figure Description
[0027] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 for β-CD 0.8 @Mela 0.2The statistical graph of the recycling performance of @Pd catalyst in the synthesis of biphenyl compounds shows the changes in product yield and catalyst loss rate during the process of catalyst reuse 7 times; Figure 2 The images shown are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the catalysts prepared in Examples 1-5 and Comparative Example 1. Figure 2 (a) SEM and TEM images of β-CD@Pd Figure 2 (b) is β-CD 0.8 @Mela 0.2 @Pd's SEM and TEM images, Figure 2 (c) is β-CD 0.6 @Mela 0.4 @Pd's SEM and TEM images, Figure 2 (d) is β-CD 0.4 @Mela 0.6 @Pd's SEM and TEM images, Figure 2 (e) is β-CD 0.2 @Mela 0.8 @Pd's SEM and TEM images, Figure 2 (f) shows the SEM and TEM images of Mela@Pd; Figure 3 These are high-magnification transmission electron microscope (TEM) images of the catalysts prepared in Examples 1-5 and Comparative Example 1, wherein... Figure 3 (a) is a high-magnification TEM image of β-CD@Pd. Figure 3 (b) is β-CD 0.8 @Mela 0.2 @Pd's high-magnification TEM image, Figure 3 (c) is β-CD 0.6 @Mela 0.4 @Pd's high-magnification TEM image, Figure 3 (d) is β-CD 0.4 @Mela 0.6 @Pd's high-magnification TEM image, Figure 3 (e) is β-CD 0.2 @Mela 0.8 @Pd's high-magnification TEM image, Figure 3 (f) is a high-magnification TEM image of Mela@Pd; Figure 4 β-CD prepared in Example 2 0.8 @Mela 0.2 Elemental distribution and energy dispersive spectroscopy (EDS) of Pd catalyst; Figure 5 The figures show the palladium elemental distribution of the catalysts prepared in Examples 1-5 and Comparative Example 1, where... Figure 5(1) is the palladium elemental distribution diagram of β-CD@Pd. Figure 5 (2) is β-CD 0.8 @Mela 0.2 Palladium distribution map of @Pd Figure 5 (3) is β-CD 0.6 @Mela 0.4 Palladium distribution map of @Pd Figure 5 (4) is β-CD 0.4 @Mela 0.6 Palladium distribution map of @Pd Figure 5 (5) is β-CD 0.2 @Mela 0.8 Palladium distribution map of @Pd Figure 5 (6) is the palladium distribution diagram of Mela@Pd; Figure 6 The X-ray diffraction (XRD) spectra of the catalysts prepared in Examples 1-5 and Comparative Example 1 are shown below. Figure 7 Fourier transform infrared (IR) spectra of the catalysts prepared in Examples 1-5 and Comparative Example 1; Figure 8 The images show the Raman spectra of the catalysts prepared in Examples 1, 2, and 1, respectively. From top to bottom, the images show the Raman spectra of catalyst β-CD@Pd, catalyst β-CD, and catalyst Pd. 0.8 @Mela 0.2 Raman spectra of @Pd and Raman spectra of the catalyst Mela@Pd; Figure 9 The X-ray photoelectron spectroscopy (XPS) spectra of the catalysts prepared in Examples 1-5 and Comparative Example 1 are shown below. Figure 9 (1) is the XPS full spectrum of β-CD@Pd. Figure 9 (2) is β-CD 0.8 @Mela 0.2 @Pd's XPS full spectrum Figure 9 (3) is β-CD 0.6 @Mela 0.4 @Pd's XPS full spectrum Figure 9 (4) is β-CD 0.4 @Mela 0.6 @Pd's XPS full spectrum Figure 9 (5) is β-CD 0.2 @Mela 0.8 @Pd's XPS full spectrum Figure 9 (6) is the XPS full spectrum of Mela@Pd; Figure 10The high-resolution X-ray photoelectron spectroscopy (C1s) spectra of the catalysts prepared in Examples 1-5 and Comparative Example 1 are shown below. Figure 10 (1) C 1s XPS analysis spectrum of β-CD@Pd Figure 10 (2) is β-CD 0.8 @Mela 0.2 @Pd's C 1s XPS analysis spectrum, Figure 10 (3) is β-CD 0.6 @Mela 0.4 @Pd's C 1s XPS analysis spectrum, Figure 10 (4) is β-CD 0.4 @Mela 0.6 @Pd's C 1s XPS analysis spectrum, Figure 10 (5) is β-CD 0.2 @Mela 0.8 @Pd's C 1s XPS analysis spectrum, Figure 10 (6) is the C 1s XPS analysis spectrum of Mela@Pd; Figure 11 The high-resolution X-ray photoelectron spectroscopy (HPS) spectra of the Pd 3d catalysts prepared in Examples 1-5 and Comparative Example 1 are shown below. Figure 11 (1) The Pd 3d XPS analysis spectrum of β-CD@Pd, Figure 11 (2) is β-CD 0.8 @Mela 0.2 @Pd's Pd 3dXPS analysis spectrum, Figure 11 (3) is β-CD 0.6 @Mela 0.4 @Pd's Pd 3d XPS analysis spectrum, Figure 11 (4) is β-CD 0.4 @Mela 0.6 @Pd's Pd 3d XPS analysis spectrum, Figure 11 (5) is β-CD 0.2 @Mela 0.8 @Pd's Pd 3d XPS analysis spectrum, Figure 11 (6) is the Pd 3d XPS analysis spectrum of Mela@Pd; Figure 12 The high-resolution X-ray photoelectron spectroscopy (XPS) spectra of the catalysts prepared in Examples 1-5 are shown below. Figure 12 (1) O 1s XPS analysis spectrum of β-CD@Pd, Figure 12 (2) is β-CD 0.8 @Mela 0.2 @Pd's O 1s XPS analysis spectrum, Figure 12(3) is β-CD 0.6 @Mela 0.4 @Pd's O 1s XPS analysis spectrum, Figure 12 (4) is β-CD 0.4 @Mela 0.6 @Pd's O 1sXPS analysis spectrum, Figure 12 (5) is β-CD 0.2 @Mela 0.8 @Pd's O 1s XPS analysis spectrum; Figure 13 The N 1s high-resolution X-ray photoelectron spectroscopy (HPS) spectra of the catalysts prepared in Examples 2-5 and Comparative Example 1 are shown below. Figure 13 (1) is β-CD 0.8 @Mela 0.2 @Pd's N 1s XPS analysis spectrum, Figure 13 (2) is β-CD 0.6 @Mela 0.4 @Pd's N1s XPS analysis spectrum, Figure 13 (3) is β-CD 0.4 @Mela 0.6 @Pd's N 1s XPS analysis spectrum, Figure 13 (4) is β-CD 0.2 @Mela 0.8 @Pd's N 1s XPS analysis spectrum, Figure 13 (5) is the N 1s XPS analysis spectrum of Mela@Pd; Figure 14 Thermogravimetric (TG) curves of the catalysts prepared in Examples 1-5 and Comparative Example 1; Figure 15 β-CD before and after 7 cycles 0.8 @Mela 0.2 The structural characterization diagram of the @Pd catalyst is shown below. Figure 15 (a) Fourier transform infrared (IR) spectra of the catalyst before and after recycling. Figure 15 (b) shows the X-ray diffraction (XRD) spectra of the catalyst before and after recycling. Detailed Implementation
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0029] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0030] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0031] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0032] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0033] To better understand the present invention, the following embodiments are provided for further illustration, but the content of the present invention is not limited to the following embodiments.
[0034] Example 1 S1: Mix 1000mg β-CD and 10mg PdCl2, and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: After thorough grinding, the mixture is transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature is increased to 350℃ at 5℃ / min and held for 1h to obtain a palladium-supported carbon-based catalyst, named β-CD@Pd.
[0035] Example 2 S1: Mix 800mg β-CD, 200mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: The thoroughly ground mixture was transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature was increased to 350℃ at 5℃ / min and held for 1 hour to obtain a palladium-supported carbon-based catalyst, named β-CD.0.8 @Mela 0.2 @Pd.
[0036] Example 3 S1: Mix 600mg β-CD, 400mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: The thoroughly ground mixture was transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature was increased to 350℃ at 5℃ / min and held for 1 hour to obtain a palladium-supported carbon-based catalyst, named β-CD. 0.6 @Mela 0.4 @Pd.
[0037] Example 4 S1: Mix 400mg β-CD, 600mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: The thoroughly ground mixture was transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature was increased to 350℃ at 5℃ / min and held for 1 hour to obtain a palladium-supported carbon-based catalyst, named β-CD. 0.4 @Mela 0.6 @Pd.
[0038] Example 5 S1: Mix 200mg β-CD, 800mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: The thoroughly ground mixture was transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature was increased to 350℃ at 5℃ / min and held for 1 hour to obtain a palladium-supported carbon-based catalyst, named β-CD. 0.2 @Mela 0.8 @Pd.
[0039] Example 6 S1: Mix 900mg β-CD, 100mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: The thoroughly ground mixture was transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature was increased to 350℃ at 5℃ / min and held for 1 hour to obtain a palladium-supported carbon-based catalyst, named β-CD. 0.9 @Mela 0.1 @Pd.
[0040] Example 7 S1: Mix 850mg β-CD, 150mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: The thoroughly ground mixture was transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature was increased to 350℃ at 5℃ / min and held for 1 hour to obtain a palladium-supported carbon-based catalyst, named β-CD. 0.85 @Mela 0.15 @Pd.
[0041] Example 8 S1: Mix 800mg β-CD, 200mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: After thorough grinding, the mixture is transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature is increased to 330℃ at 4℃ / min and held for 1.5h to obtain a palladium-supported carbon-based catalyst.
[0042] Example 9 S1: Mix 800mg β-CD, 200mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: After thorough grinding, the mixture is transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature is increased to 360℃ at 6℃ / min and held for 2 hours to obtain a palladium-supported carbon-based catalyst.
[0043] Example 10 S1: Mix 800mg β-CD, 200mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: After thorough grinding, the mixture is transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature is increased to 340℃ at 4℃ / min and held for 1.5h to obtain a palladium-supported carbon-based catalyst.
[0044] Comparative Example 1 S1: Mix 1000mg Mela and 10mg PdCl2 and grind them in a ball mill at 50Hz for 60 minutes to obtain a mixture. S2: After thorough grinding, the mixture is transferred to a crucible and placed in a tube furnace for calcination. Under argon protection, the temperature is increased to 350℃ at 5℃ / min and held for 1h to obtain the catalyst, named Mela@Pd.
[0045] Application Example 1 1 mmol of iodobenzene, 1.5 mmol of phenylboronic acid, 2 mL of EtOH:H2O 1:1 solvent, 2 mmol of K2CO3, and 10 mg of the catalyst β-CD@Pd prepared in Example 1 were added to a 15 mL reaction tube. The reaction tube was placed in a heating pan and heated to 90 °C. The reaction was monitored by TLC while the reaction proceeded. The reaction was completed after 24 h. After the reaction system cooled, it was filtered, and the catalyst was repeatedly washed with ethyl acetate, separated, and dried for later use. Liquid chromatography was performed using saturated brine, followed by drying with anhydrous sodium sulfate. Finally, the product was purified by column chromatography using pure petroleum ether as the eluent. The structure of the obtained product was determined by nuclear magnetic resonance, and the weight calculation confirmed that 98% of the target product was obtained. The reaction equation is as follows: .
[0046] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.79 (dd, J = 7.4, 1.8 Hz, 4H), 7.66 – 7.57 (m, 4H), 7.52 (td, J = 7.2, 1.4 Hz, 2H). 13 C NMR (101 MHz, CDCl3)δ 141.65, 129.20, 127.69, 127.60. Application Example 2 The only difference from Application Example 1 is that the catalyst used is the β-CD catalyst prepared in Example 6. 0.9 @Mela 0.1 @Pd, all other conditions and steps are exactly the same as in Application Example 1, and weighing and calculation confirmed that 96% of the target product was obtained. The reaction equation is as follows: .
[0047] Application Example 3 The only difference from Application Example 1 is that the catalyst used is the β-CD catalyst prepared in Example 7. 0.85 @Mela 0.15 @Pd, all other conditions and steps are exactly the same as in Application Example 1, and weighing and calculation confirmed that 96% of the target product was obtained. The reaction equation is as follows: .
[0048] Application Example 4 The only difference from Application Example 1 is that the catalyst used is the β-CD catalyst prepared in Example 2. 0.8 @Mela 0.2@Pd, all other conditions and steps are exactly the same as in Application Example 1, and weighing and calculation confirmed that 96% of the target product was obtained. The reaction equation is as follows: .
[0049] Application Example 5 Compared to Application Example 1, the only difference is that the catalyst used is the β-CD catalyst prepared in Example 3. 0.6 @Mela 0.4 @Pd, all other conditions and steps are exactly the same as in Application Example 1, and weighing and calculation confirmed that 82% of the target product was obtained. The reaction equation is as follows: .
[0050] Application Example 6 The only difference from Application Example 1 is that the catalyst used is the β-CD catalyst prepared in Example 4. 0.4 @Mela 0.6 @Pd, all other conditions and steps are exactly the same as in Application Example 1, and weighing and calculation confirmed that 78% of the target product was obtained. The reaction equation is as follows: .
[0051] Application Example 7 Compared to Application Example 1, the only difference is that the catalyst used is the β-CD catalyst prepared in Example 5. 0.2 @Mela 0.8 @Pd, all other conditions and steps are exactly the same as in Application Example 1, and weighing and calculation confirmed that 75% of the target product was obtained. The reaction equation is as follows: .
[0052] Comparative Application Example 1 Compared to Application Example 1, the only difference was that the catalyst used was Mela@Pd prepared in Comparative Example 1; all other conditions and procedures were exactly the same as in Application Example 1. The structure of the obtained product was finally determined using nuclear magnetic resonance (NMR), and weighing calculations confirmed that it contained 70% of the target product.
[0053] The reaction equation is as follows: .
[0054] The key parameters of Application Examples 1-7 and Comparative Application Example 1 are summarized in Table 1 below. Table 1. Summary of key parameters between Application Examples 1-7 and Comparative Application Example 1 ; As shown in Table 1, the product yield generally increases with the increase of the β-CD ratio during catalyst preparation. The catalyst material β-CD@Pd prepared by using β-CD and PdCl2 alone has the best catalytic effect, with a product yield as high as 98%. On the other hand, the catalyst material Mela@Pd prepared by using Mela and PdCl2 alone has the worst catalytic effect, with a product yield of only 70%. The reason for this problem is that although Mela can be used as a metal support, its surface activity is very poor, which prevents the catalyst and the reaction substrate from making sufficient contact in the liquid phase reaction.
[0055] Application Example 8 The catalyst β-CD prepared in Example 2 was prepared by mixing 1 mmol of iodobenzene, 1.5 mmol of phenylboronic acid, 1 mL of EtOH, 2 mmol of K2CO3, and 10 mg of... 0.8 @Mela 0.2 @Pd was added to a 15ml reaction tube, which was then placed in a heating pan and heated to 90℃. The reaction was monitored by TLC during the reaction, which ended after 24 hours. After the reaction system cooled, it was filtered, and the catalyst was repeatedly washed with ethyl acetate. After separation, it was dried for future use. Extraction was performed in liquid chromatography with saturated brine, followed by drying with anhydrous sodium sulfate. Finally, the product was purified by column chromatography using pure petroleum ether as the eluent. The structure of the obtained product was determined by nuclear magnetic resonance, and the weight calculation confirmed that it contained 99% of the target product. The reaction equation is as follows: .
[0056] Application Example 9 Compared with Application Example 8, the only difference is that the solvent is 1 mL H2O. All other conditions and steps are exactly the same as in Application Example 8, and the calculated yield is 90%.
[0057] The reaction equation is as follows: .
[0058] Application Example 10 Compared with Application Example 8, the only difference is that the solvent is a 1 mL EtOH:H2O 1:1 mixed solvent. All other conditions and steps are exactly the same as in Application Example 8, and the calculated yield is 96%.
[0059] The reaction equation is as follows: .
[0060] Application Example 11 Compared with Application Example 10, the only difference is that the reaction time is 12 hours. All other conditions and steps are exactly the same as in Application Example 10, and the calculated yield is 96%.
[0061] Application Example 12 Compared with Application Example 10, the only difference is that the reaction time is 5 hours. All other conditions and steps are exactly the same as in Application Example 10, and the calculated yield is 96%.
[0062] Application Example 13 Compared with Application Example 10, the only difference is that the reaction time is 3 hours. All other conditions and steps are exactly the same as in Application Example 10, and the calculated yield is 88%.
[0063] Application Example 14 Compared to Application Example 8, the only difference is the catalyst β-CD. 0.8 @Mela 0.2 The dosage of Pd was 5 mg, the reaction time was 5 h, and other conditions and steps were exactly the same as in Application Example 8. The calculated yield was 96%.
[0064] Application Example 15 Compared with Application Example 14, the only difference is that the reaction temperature is 100°C. All other conditions and steps are exactly the same as in Application Example 14, and the calculated yield is 96%.
[0065] Application Example 16 Compared with Application Example 14, the only difference is that the reaction temperature is 80°C. All other conditions and steps are exactly the same as in Application Example 14, and the calculated yield is 90%.
[0066] The key parameters of Application Examples 8-16 and Comparative Application Example 1 are summarized in Table 2 below.
[0067] Table 2. Summary of key parameters between Application Examples 8-16 and Comparative Application Example 1 ; As shown in Table 2, the highest yield (99%) was achieved when ethanol was used as the solvent. Considering the overall environmental friendliness, the ethanol-water (1:1) mixed solvent was selected. The highest yield of 96% was achieved after 5 hours of reaction, and there was no improvement after further extending the reaction time. The yield remained unchanged when the catalyst dosage was reduced from 10 mg to 5 mg. The yield was comparable at 90℃ and 100℃, but dropped to 90% at 80℃.
[0068] Application Example 17 The catalyst β-CD prepared in Example 2 was prepared by mixing 1 mmol of iodobenzene, 1.5 mmol of p-methylphenylboronic acid, 1 mL of a 1:1 mixture of EtOH and H2O, 2 mmol of K2CO3, and 10 mg of [a specific solvent]. 0.8 @Mela 0.2@Pd was added to a 15ml reaction tube, which was then placed in a heating pan and heated to 90℃. The reaction was monitored by TLC while the reaction proceeded, and the reaction was considered complete after 5 hours. After the reaction system cooled, it was filtered, and the catalyst was repeatedly washed with ethyl acetate. After separation, the catalyst was dried for future use. Liquid chromatography was performed using saturated brine, followed by drying with anhydrous sodium sulfate. Finally, the product was purified using pure petroleum ether as the eluent for column chromatography. The structure of the obtained product was determined by nuclear magnetic resonance, and the weight calculation confirmed that 94% of the target product was present. The reaction equation is as follows: .
[0069] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.55 (dt, J = 7.0, 1.9 Hz, 2H), 7.47 (dt, J = 8.1, 1.9 Hz, 2H), 7.39 (tt, J = 8.0, 1.7 Hz, 2H), 7.29 (ddd, J= 9.0, 5.3, 1.7 Hz, 1H), 7.21 (d, J = 7.8 Hz, 2H), 2.36 (t, J = 1.6 Hz, 3H). 13 C NMR (100 MHz, CDCl3) δ 141.08, 138.28, 136.93, 129.44, 128.67, 126.94,126.92, 21.05. Application Example 18 Compared to Application Example 17, the only difference is that the arylboronic acid compound is 3-methylphenylboronic acid; all other conditions and steps are exactly the same as in Application Example 17, and the calculated yield is 93%. The reaction equation is as follows:
[0070] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, DMSO-d6) δ 7.66(d, J = 7.3 Hz, 2H), 7.51 –7.43 (m,4H), 7.41 – 7.30 (m, 2H), 7.19 (d, J = 7.2 Hz, 1H), 2.39 (s, 3H). 13C NMR (100 MHz, DMSO) δ = 140.83, 140.69, 138.50, 129.33, 129.27, 128.52, 127.84, 127.78, 127.15, 124.26, 21.57.
[0071] Application Example 19 Compared to Application Example 17, the only difference is that the arylboronic acid compound is 4-fluorophenylboronic acid; all other conditions and steps are exactly the same as in Application Example 17, and the calculated yield is 99%. The reaction equation is as follows: .
[0072] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.49 (d, J = 7.5 Hz, 4H), 7.38 (t,J = 7.6 Hz, 2H), 7.30 (t, J = 7.4 Hz, 1H), 7.07 (t, J = 8.5 Hz, 2H). 13 C NMR (100 MHz, CDCl3) δ 163.83, 161.38, 140.35, 137.46, 137.43, 128.97, 128.85,128.77, 127.41, 127.15, 115.86, 115.64. Application Example 20 Compared to Application Example 17, the only difference is that the arylboronic acid compound is 4-methoxyphenylboronic acid; all other conditions and steps are exactly the same as in Application Example 17, and the calculated yield is 98%. The reaction equation is as follows: .
[0073] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.42 (t, J = 9.2 Hz, 4H), 7.29 (t,J = 7.6 Hz, 2H), 7.18 (t, J = 7.4 Hz, 1H), 6.85 (d, J = 8.2 Hz, 2H), 3.70 (s,3H). 13 C NMR (100 MHz, CDCl3) δ 159.06, 140.72, 133.64, 128.67, 128.07,126.65, 126.59, 114.12, 55.21. Application Example 21 The catalyst β-CD prepared in Example 2 was prepared by mixing 1 mmol of p-iodotoluene, 1.5 mmol of phenylboronic acid, 1 mL of a 1:1 EtOH:H2O mixed solvent, 2 mmol of K2CO3, and 10 mg of the catalyst prepared in Example 2. 0.8 @Mela 0.2 @Pd was added to a 15ml reaction tube, which was then placed in a heating pan and heated to 90℃. The reaction was monitored by TLC while the reaction proceeded, and the reaction was considered complete after 5 hours. After the reaction system cooled, it was filtered, and the catalyst was repeatedly washed with ethyl acetate. After separation, the catalyst was dried for future use. Extraction was performed in liquid chromatography using saturated brine, followed by drying with anhydrous sodium sulfate. Finally, the product was purified by column chromatography using pure petroleum ether as the eluent. The structure of the obtained product was determined by nuclear magnetic resonance, and the weight calculation confirmed that 97% of the target product was present.
[0074] The reaction equation is as follows: .
[0075] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.55 (dt, J = 7.0, 1.9 Hz, 2H), 7.47 (dt, J = 8.1, 1.9 Hz, 2H), 7.39 (tt, J = 8.0, 1.7 Hz, 2H), 7.29 (ddd, J= 9.0, 5.3, 1.7 Hz, 1H), 7.21 (d, J = 7.8 Hz, 2H), 2.36 (t, J = 1.6 Hz, 3H). 13 C NMR (100 MHz, CDCl3) δ 141.08, 138.28, 136.93, 129.44, 128.67, 126.94,126.92, 21.05. Application Example 22 Compared to Application Example 21, the only difference is that the haloaromatic hydrocarbon is 4-iodobenzaldehyde; all other conditions and steps are exactly the same as in Application Example 21, and the calculated yield is 98%. The reaction equation is as follows: .
[0076] Nuclear magnetic resonance characterization: 1H NMR ( 400 MHz, DMSO-d6) δ 10.08 (s, 1H), 8.03 (d, J 8.0Hz, 2H), 7.91 (d, J = 8.0 Hz, 2H), 7.79 (d, J = 7.6 Hz, 2H), 7.52 (t, J 7.5Hz, 2H), 7.47 (t, J 7.3 Hz, 1H). 13 C NMR (100 MHz, DMSO) δ 193.19, 146.36, 139.28, 135.59, 130.62, 129.60, 129.03, 127.84, 127.57.
[0077] Application Example 23 Compared to Application Example 21, the only difference is that the haloaromatic hydrocarbon is 4-iodoacetophenone; all other conditions and steps are exactly the same as in Application Example 21, and the calculated yield is 88%. The reaction equation is as follows: .
[0078] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3): δ 8.06 (d, J = 8.0 Hz, 2H), 7.67 (d,J = 8.0 Hz, 2H), 7.68 (d, J = 7.5 Hz, 2H), 7.48 (d, J = 7.2 Hz, 2H), 7.41 (t,J = 6.5 Hz, 1H), 2.65 (s, 3H). 13 C NMR (100 MHz, CDCl3, ppm): δ 197.80,145.82, 139.91, 135.89, 129.01, 128.89, 128.23, 127.31, 127.23, 26.68.
[0079] Application Example 24 Compared to Application Example 21, the only difference is that the haloaromatic hydrocarbon is 4-iodoanisole; all other conditions and steps are exactly the same as in Application Example 21, and the calculated yield is 88%. The reaction equation is as follows: .
[0080] Nuclear magnetic resonance characterization: 1H NMR (400 MHz, CDCl3) δ 7.42 (t, J = 9.2 Hz, 4H), 7.29 (t,J = 7.6 Hz, 2H), 7.18 (t, J = 7.4 Hz, 1H), 6.85 (d, J = 8.2 Hz, 2H), 3.70 (s,3H). 13 C NMR (100 MHz, CDCl3) δ 159.06, 140.72, 133.64, 128.67, 128.07,126.65, 126.59, 114.12, 55.21. Application Example 25 Compared to Application Example 20, the only difference is that the haloaromatic hydrocarbon is p-fluoroiodobenzene; all other conditions and steps are exactly the same as in Application Example 21, and the calculated yield is 98%. The reaction equation is as follows: .
[0081] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.49 (d, J = 7.5 Hz, 4H), 7.38 (t, J =7.6 Hz, 2H), 7.30 (t, J = 7.4 Hz, 1H), 7.07 (t, J = 8.5 Hz, 2H). 13 C NMR (100 MHz, CDCl3) δ 163.83, 161.38, 140.35, 137.46, 137.43, 128.97, 128.85, 128.77,127.41, 127.15, 115.86, 115.64. Application Example 26 Compared to Application Example 20, the only difference is that the haloaromatic hydrocarbon is p-chloroiodobenzene; all other conditions and steps are exactly the same as in Application Example 20, and the calculated yield is 97%. The reaction equation is as follows: .
[0082] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.52 – 7.47 (m, 2H), 7.47 – 7.43 (m, 2H), 7.44 – 7.26 (m, 5H). 13C NMR (100 MHz, CDCl3) δ 139.86, 139.55, 133.30, 128.83, 128.32, 127.53, 126.90. Application Example 27 Compared to Application Example 20, the only difference is that the haloaromatic hydrocarbon is p-bromoiodobenzene; all other conditions and steps are exactly the same as in Application Example 20, and the calculated yield is 82%. The reaction equation is as follows: .
[0083] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.59 – 7.49 (m, 4H), 7.42 (dd, J =8.3, 6.6 Hz, 4H), 7.39 – 7.30 (m, 1H). 13 C NMR (100 MHz, CDCl3) δ 140.05,139.93, 131.81, 128.86, 128.70, 127.60, 126.90, 121.50. Application Example 28 Compared to Application Example 20, the only difference is that the haloaromatic hydrocarbon is 1-iodonaphthalene; all other conditions and steps are exactly the same as in Application Example 20, and the calculated yield is 93%. The reaction equation is as follows: .
[0084] Nuclear magnetic resonance characterization: 1 H NMR (400 MHz, CDCl3) δ 7.89 (d, J = 8.4 Hz, 1H), 7.80 (d,J = 8.2 Hz, 1H), 7.75 (d, J = 8.3 Hz, 1H), 7.46 – 7.28 (m, 9H). 13 C NMR (100MHz, CDCl3) δ 140.68, 140.17, 133.74, 131.55, 130.00, 128.22, 128.19, 127.58,127.15, 126.88, 125.97, 125.96, 125.70, 125.32. Application Example 29 Compared with Application Example 20, the only difference is that the halogenated aromatic hydrocarbon is bromobenzene. All other conditions and steps are exactly the same as in Application Example 20, and the calculated yield is 75%.
[0085] The reaction equation is as follows: .
[0086] The key parameters of application examples 17-29 and comparison example 1 are summarized in Table 3 below:
[0087] Table 3. Summary of key parameters for application examples 17-29
[0088] As shown in Table 1, Application Examples 17-29 use the catalyst β-CD. 0.8 @Mela 0.2 @Pd catalysis yielded a variety of biphenyl compounds from halogenated aromatic hydrocarbons and arylboronic acid compounds with different functional groups. For example, when the halogenated aromatic hydrocarbon was the heterocyclic iodide 2-iodonaphthalene, the catalyst could achieve a yield of up to 93% for the reaction of 2-iodonaphthalene. In the coupling of bromobenzene, an arylboronic acid compound, the yield could reach 75%. These applications demonstrate the high efficiency and versatility of the catalyst of this invention.
[0089] Application Example 30 Scale-up experiment: 20 mmol of iodobenzene, 30 mmol of phenylboronic acid, 20 mL of a 1:1 EtOH:H2O mixed solvent, 40 mmol of K2CO3, and 200 mg of the catalyst β-CD prepared in Example 2 were mixed. 0.8 @Mela 0.2 @Pd was added to a 100ml reaction tube, which was then placed in a heating pan and heated to 90℃. The reaction was monitored by TLC while the reaction proceeded, and the reaction was considered complete after 5 hours. After the reaction system cooled, it was filtered, and the catalyst was repeatedly washed with ethyl acetate. After separation, the catalyst was dried for future use. Liquid chromatography was performed using saturated brine, followed by drying with anhydrous sodium sulfate. Finally, the product was purified using pure petroleum ether as the eluent for column chromatography. The structure of the obtained product was determined by nuclear magnetic resonance, and the weight calculation confirmed that 94% of the target product was present.
[0090] Throughout the process, cyclodextrin acted as a surfactant in the catalyst system, enabling the catalyst to fully contact the substrate and achieve better reaction results. Simultaneously, the addition of melamine improved the stability of the catalyst system. Experiments fully demonstrated the high efficiency and environmental friendliness of the catalyst.
[0091] Application Example 31 Recycling experiment: 20 mmol of iodobenzene, 30 mmol of phenylboronic acid, 20 mL of a 1:1 EtOH:H2O mixed solvent, 40 mmol of K2CO3, and 200 mg of the catalyst β-CD prepared in Example 2 were used. 0.8 @Mela 0.2@Pd was added to a 100ml reaction tube, which was then placed in a heating pan and heated to 90℃. The reaction was monitored by TLC during the reaction process. After 5 hours, the reaction system was cooled, and the product yield was calculated after post-processing. The catalyst solid obtained by filtering the reaction system was dried in a vacuum drying oven for 6 hours, and the mass of the collected solid was recorded as M. x (x is the number of repeated experiments). Then, the mass M x The catalyst is added to the next identical cycle reaction, and the same steps are repeated for a total of 7 reactions. The product yield and catalyst loss rate are calculated, where catalyst loss rate = (M... x -M x+1 ) / M x *100%.
[0092] The statistical graph of product yield and catalyst loss rate in the recycling experiment is shown below. Figure 1 As shown, by Figure 1 It can be seen that: β-CD 0.8 @Mela 0.2 The Pd catalyst exhibited good stability in the cyclic experiment of catalytic synthesis of biphenyl compounds (Suzuki coupling reaction), yielding 86% of the target product after 7 cycles, a decrease compared to the 96% yield obtained in the first reaction. The main reasons for this are: 1) mass loss caused by human intervention during the experiment; nanoscale catalysts are difficult to recover completely during filtration and recycling; 2) with increasing cycle count, some metal exposed on the catalyst surface is lost during repeated washing, reducing the number of active sites and thus decreasing the catalytic effect.
[0093] Structure and Representation 1. SEM and TEM 1) Catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 0.8 @Mela 0.2 @Pd、β-CD 0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6 @Pd、β-CD 0.2 @Mela 0.8 @Pd and Mela@Pd were characterized by SEM and TEM, and the characterization images are shown below. Figure 2As shown, morphological observation at the 10µm scale (Figs. a2-f2) reveals that the catalyst morphology changes with increasing Mela ratio. Although it appears to have a porous structure, BET testing confirms that the catalyst has a very small specific surface area and is not porous. This indicates that the active centers of the catalyst are not located in the surface morphology and pore size, but rather in the coordination of O and N elements with the metal on β-CD and Mela. The TEM images (a4-f4) clearly show the lattice fringes formed by palladium on the composite material.
[0094] 2) Catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 0.8 @Mela 0.2 @Pd、β-CD 0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6 @Pd、β-CD 0.2 @Mela 0.8 TEM images of @Pd and Mela@Pd are as follows Figure 3 As shown, Figure 3 The images showcase the results of high-magnification transmission electron microscopy (TEM). Metallic lattice fringes are clearly visible in the images. A detailed comparison with standard PDF cards is provided, detailing the lattice spacing exhibited by catalysts with different β-CD / Mela ratios. Figure 3 (a) is a TEM image of β-CD@Pd, mainly showing lattice spacings of d=0.237nm and d=0.213nm, which represent (111) and (311) crystal planes, respectively; Figure 3 (b) is β-CD 0.8 @Mela 0.2 The TEM image of @Pd shows that the lattice spacing d = 0.228 nm, which corresponds to the (211 crystal plane). Figure 3 (c) is β-CD 0.6 @Mela 0.4 TEM image of @Pd, lattice spacing d=0.221nm, corresponding to (410 crystal plane); Figure 3 (d) Figure 3 (e) represent β-CD 0.4 @Mela 0.6 @Pd and β-CD 0.2 @Mela 0.8 TEM images of @Pd show that the lattice spacings of the two crystals are d=0.181nm and d=0.178nm, respectively, both corresponding to the (220) crystal plane; Figure 3 (f) is a TEM image of Mela@Pd with a lattice spacing of d=0.275nm, showing the (400) crystal plane.
[0095] 2. Elemental distribution and EDS Figure 4 Catalyst β-CD in Example 2 0.8 @Mela 0.2 The elemental distribution and EDS plot of @Pd show that during the recombination process, the elements interact with each other, are evenly distributed, and no aggregation occurs.
[0096] The catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 were compared. 0.8 @Mela 0.2 @Pd、β-CD 0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6 @Pd、β-CD 0.2 @Mela 0.8 Further palladium distribution characterization was performed on @Pd and Mela@Pd, as shown in the characterization figures. Figure 5 As shown in the figure. It can be seen from the figure that β-CD@Pd (using β-CD as the carrier alone) Figure 5 (1) and Mela@Pd (using Mela as the carrier alone) Figure 5 In (6), palladium exhibits significant aggregation; while the catalyst supported on the β-CD and Mela composite support ( Figure 5 In (2)~(5), palladium is uniformly distributed on the support material, indicating that the synergistic effect of β-CD and Mela provides a good dispersion environment for palladium and effectively inhibits the aggregation of palladium nanoparticles.
[0097] Meanwhile, the elemental content of catalysts with different ratios was quantitatively analyzed, and the results are shown in Table 4. As can be seen from the table, with the increase of the Mela ratio in the support, the N element content in the catalyst gradually increases, the O element content gradually decreases, the C element content fluctuates, while the Pd element content remains consistently between 1 and 2 wt%.
[0098] Table 4. Elemental distribution of catalyst systems with different ratios
[0099] 3. Specific surface area and pore structure analysis The catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 were tested. 0.8 @Mela 0.2 @Pd、β-CD 0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6@Pd、β-CD 0.2 @Mela 0.8 The specific surface area and pore structure characteristics of @Pd and Mela@Pd materials are shown in Table 5.
[0100] Table 5. Test data on specific surface area and pore structure characteristics of different catalysts
[0101] As shown in Table 5, the specific surface area of all catalysts is relatively small, ranging from 0.5448 to 4.4501 m². 2 The pore volume ranges from 0.002040 to 0.104379 cm³ / g. 3 The average pore size is between 5.3618 and 19.1325 nm, which confirms that the catalyst is not porous and that the pore structure is not the main factor affecting the catalytic activity. This further indicates that the active center of the catalyst comes from the coordination of O and N elements on β-CD and Mela with palladium.
[0102] 4. X-ray diffraction (XRD) analysis The catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 were compared. 0.8 @Mela 0.2 @Pd、β-CD 0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6 @Pd、β-CD 0.2 @Mela 0.8 X-ray diffraction characterization was performed on @Pd and Mela@Pd to analyze their crystal structure. The XRD patterns are shown below. Figure 6 As shown. By Figure 6 The XRD patterns show that all samples exhibit a major diffraction peak at 2θ = 13.6°, which is attributed to the characteristic diffraction region of carbon in cyclodextrin and melamine. Simultaneously, four major diffraction peaks appear at 2θ = 39.3°, 39.8°, 46.6°, and 67.9°, respectively, which correspond to the Pd(211), Pd(111), Pd(200), and Pd(220) crystal phases of palladium. This confirms that palladium exists in a crystalline form within the catalyst, and that the palladium crystal phase differs among catalysts with different β-CD to Mela ratios, consistent with the lattice spacing results obtained from TEM characterization.
[0103] 5. Fourier transform infrared spectroscopy analysis The catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 were compared. 0.8 @Mela 0.2 @Pd、β-CD0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6 @Pd、β-CD 0.2 @Mela 0.8 Fourier transform infrared spectroscopy was performed on @Pd and Mela@Pd to analyze their surface functional group structure. The IR spectra are shown below. Figure 7 As shown.
[0104] As can be seen from the IR spectrum, in the β-CD@Pd catalyst with β-CD as the support alone, the 3428 cm⁻¹... -1 The absorption peak at 2933 cm⁻¹ is attributed to the hydroxyl group (-OH). -1 The absorption peak at 1110 cm⁻¹ is attributed to an aliphatic carbon-hydrogen bond (-CH). -1 The absorption peak at 1445 cm⁻¹ is attributed to the carbon-oxygen bond (CO); in the Mela@Pd catalyst supported solely on Mela, the peak at 1445 cm⁻¹ is... -1 The absorption peak at that point is attributed to the carbon-nitrogen bond (CN).
[0105] In the composite catalyst material formed after β-CD and Mela are doped, the absorption peaks of -OH, -CH, and -CO in the catalyst exhibit a red shift, while the absorption peak of -CN exhibits a blue shift. For example, β-CD... 0.8 @Mela 0.2 In the spectrum of the Pd catalyst, the absorption peaks of -OH and -CH shifted to 3438 cm⁻¹. -1 2936cm -1 The absorption peak of -CN shifted to 1428 cm⁻¹. -1 The shifts in the absorption peaks of these major functional groups indicate that an interaction occurred during the preparation of the β-CD and Mela-doped composite catalyst, resulting in the formation of new chemical bond structures, i.e., the emergence of new functional group structures.
[0106] 6. Raman spectroscopy analysis For catalysts β-CD@Pd, β-CD 0.8 @Mela 0.2 Raman spectroscopy was performed on @Pd and Mela@Pd to analyze their structural characteristics as carbon materials. The Raman spectra are shown below. Figure 8 As shown.
[0107] The Raman spectrum shows that the β-CD@Pd catalyst exhibits high performance at 1366 cm⁻¹. -1 The location represented by sp appeared. 3 The D-band absorption peak of the configuration carbon is at 1579 cm⁻¹. -1A G-band absorption peak representing graphitic carbon appeared at [location missing]. When Mela was doped into the support, the absorption peak intensities of the D and G bands changed, with β-CD [details missing]. 0.8 @Mela 0.2 The ID / IG value of the @Pd catalyst is 0.9141, indicating that the introduction of melamine gives the composite catalyst more crystallinity and structural defects. These defect sites can provide more coordination sites for palladium, which is beneficial to improving the catalytic activity of the catalyst.
[0108] 7. X-ray photoelectron spectroscopy analysis The catalysts prepared in Examples 1-5 and Comparative Example 1 were characterized by X-ray photoelectron spectroscopy (XPS) to analyze their surface elemental composition and chemical valence states. The full XPS spectra are shown below. Figure 9 As shown.
[0109] from Figure 9 The XPS full spectrum shows that as the proportion of Mela in the support increases, the binding energy signal of C in the catalyst gradually weakens, while the binding energy signal of N gradually strengthens, which is consistent with the results of elemental quantitative analysis.
[0110] The C 1s elemental analysis diagram of the catalyst system is shown below. Figure 10 As shown in the figure, the β-CD@Pd catalyst mainly contains three types of chemical bonds: C=O, CO, and CC. 0.8 @Mela 0.2 @Pd catalysts begin to form CN chemical bonds, β-CD 0.6 @Mela 0.4 In @Pd, the C=O double bond has been masked and disappeared by CN and CO; as the Mela ratio further increases, the signal intensity of CN / CO gradually increases, while the signal intensity of C=O gradually decreases until it disappears, indicating that β-CD and Mela have undergone chemical bonding under the bridging effect of palladium.
[0111] The elemental analysis diagram of Pd 3d in the catalyst system is shown below. Figure 11 As shown in the figure, the XPS spectrum of Pd 3d exhibits low-energy Pd 3d. 5 / 2 High-energy Pd 3d 3 / 2 The two-state structure of the band, where Pd 3d 5 / 2 The binding energy is approximately 337.6 eV, Pd 3d 3 / 2 The binding energy is approximately 342.7 eV. These bands consist of two pairs belonging to the metallic Pd. 0 and Pd oxide 2+ The dual-state composition, and Pd 0The proportion of β-CD decreases as the proportion of β-CD decreases, indicating that during calcination under argon protection, β-CD molecules can effectively reduce palladium chloride to zero-valent palladium, providing the main active sites for the catalyst.
[0112] The elemental analysis diagram of O 1s in the catalyst system is shown below. Figure 12 As shown in the figure, oxygen in the catalyst mainly exists in the forms of C=O, COC / COH, and Pd-O. The large amount of oxygen introduced by β-CD enhances the hydrophilicity of the catalyst, which helps to improve the catalyst's activity in liquid-phase reactions.
[0113] The N 1s analysis chromatogram of the catalyst system is shown below. Figure 13 As shown in the figure, nitrogen in the composite catalyst mainly exists in four forms: pyridinic N, pyrrolic N, graphitic N, and oxidized N, located at 398.4±eV, 399.4±eV, 400±eV, and 401±eV, respectively. These different nitrogen forms provide additional active sites for the composite material, enabling it to form stable coordination bonds with palladium, thereby improving the catalyst's stability.
[0114] The combined XPS analysis results confirmed the formation of CO-Pd and CN-Pd chemical bonds in the composite catalyst, which is the fundamental reason for the catalyst's high activity and high stability.
[0115] 8. Thermogravimetric analysis The catalysts β-CD@Pd and β-CD prepared in Examples 1-5 and Comparative Example 1 were compared. 0.8 @Mela 0.2 @Pd、β-CD 0.6 @Mela 0.4 @Pd、β-CD 0.4 @Mela 0.6 @Pd、β-CD 0.2 @Mela 0.8 Thermogravimetric (TG) analysis was performed on @Pd and Mela@Pd to characterize their thermal stability. The TG curves are shown below. Figure 14 As shown in the figure, the thermal weight loss process of all catalysts mainly consists of two stages: the first stage occurs at around 300℃, where the weight loss is primarily caused by the pyrolysis of β-CD; the second stage occurs at around 700℃, where the weight loss is mainly caused by the loss of amino groups. With the increase of the proportion of Mela in the support, the total weight loss rate of the catalyst gradually increases. Specifically, the total weight loss rate of β-CD@Pd is 32%, while that of Mela@Pd is 100%, indicating that the thermal stability of melamine is lower than that of β-CD.
[0116] 9. Structural characterization of the catalyst after recycling For example 31, the catalyst after 7 cycles was characterized by infrared spectroscopy and X-ray diffraction. The catalyst that was not reused was denoted as β-CD@Mela@Pd, and the catalyst that was reused seven times was denoted as β-CD@Mela@Pd-7. The characterization figures are shown below. Figure 15 As shown. From the infrared spectrum ( Figure 15 (a) shows that after 7 cycles, the absorption peak positions of the main functional groups in the catalyst β-CD@Mela@Pd-7 did not shift significantly, indicating that the main functional group structure of the catalyst was effectively preserved. This is an important reason why the catalyst can still maintain high activity during recycling. From the X-ray diffraction pattern ( Figure 15 (b) It can be seen that after 7 cycles, the main characteristic diffraction peaks of the support material in the catalyst β-CD@Mela@Pd-7 did not change significantly, but the intensity of the characteristic diffraction peak of palladium was significantly reduced, indicating that some palladium was lost from the catalyst surface, resulting in a reduction in the number of active centers. This is the main reason for the slight decrease in activity of the catalyst after recycling.
[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a palladium-supported carbon-based catalyst, characterized in that, Includes the following steps: S1: The carrier material and palladium chloride are mixed and then ground to obtain a mixture. S2: The mixture is heated and then calcined to obtain a palladium-supported carbon-based catalyst.
2. The method for preparing the palladium-supported carbon-based catalyst according to claim 1, characterized in that, The mass ratio of the carrier material to palladium chloride is 100:
1.
3. The method for preparing the palladium-supported carbon-based catalyst according to claim 2, characterized in that, In the carrier material, the proportion of β-cyclodextrin is 20wt%~100wt%, and the proportion of melamine is 0~80wt%.
4. The method for preparing the palladium-supported carbon-based catalyst according to claim 3, characterized in that, In the carrier material, β-cyclodextrin accounts for 80 wt% and melamine accounts for 20 wt%.
5. The method for preparing the palladium-supported carbon-based catalyst according to any one of claims 1 to 4, characterized in that, The grinding was carried out in a ball mill at 50 Hz.
6. The method for preparing the palladium-supported carbon-based catalyst according to any one of claims 1 to 5, characterized in that, The heating rate is 4~6℃ / min; the calcination is carried out under argon protection, the calcination temperature is 330~360℃, and the calcination time is 1~2h.
7. A palladium-supported carbon-based catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. A method for preparing a palladium-supported carbon-based catalyst as described in claim 7 and its application in the Suzuki coupling reaction, characterized in that, The reaction for synthesizing the biphenyl compounds is as follows: a Suzuki coupling reaction is carried out after mixing the haloaromatic hydrocarbon shown in Formula I, the arylboronic acid compound shown in Formula II, the palladium-supported carbon-based catalyst, the solvent, and the base to obtain the biphenyl compound shown in Formula III. The reaction equations for the synthesis of the biphenyl compounds are as follows: ; Wherein, R1 includes an aryl or substituted aryl group, wherein the substituents of the substituted aryl group include C1-C1. 10 Alkyl, C1-C 10 Alkoxy, halogenated C1-C 10 Alkyl, halogenated C1-C 10 Alkyl, halogen, cyano, nitro, acetyl, aldehyde, carboxyl, ester, or hydroxyl groups; X includes Br or I; R2 includes hydrogen, halogens, and C1-C. 10 Alkyl, C1-C 10 Alkoxy, halogenated C1-C 10 Alkyl, halogenated C1-C 10 Alkoxy; The addition ratio of the haloaromatic hydrocarbons shown in Formula I, the arylboronic acid compounds shown in Formula II, and the palladium-supported carbon-based catalyst is 1 mmol: 1.5 mmol: (5~10) mg; The addition ratio of the halogenated aromatic hydrocarbon, solvent and base shown in Formula I is 1 mmol: 1~2 mL: 2 mmol; The solvent includes ethanol, water, and a mixture of ethanol and water, wherein the volume ratio of ethanol to water in the mixture of ethanol and water is 1:
1. The alkali includes potassium carbonate, sodium carbonate, potassium acetate, sodium acetate, potassium phosphate, sodium phosphate, triethylamine, cesium carbonate, sodium hydroxide, or potassium hydroxide; The reaction temperature for synthesizing the biphenyl compounds is 80~100℃, and the reaction time is 3~24h.
9. The preparation of the palladium-supported carbon-based catalyst according to claim 8 and its application in the Suzuki coupling reaction, characterized in that, R1 is phenyl, naphthyl, or a substituted phenyl group; The substituents of the substituted phenyl group are C1-C4 alkyl, C1-C4 alkoxy, halogenated C1-C4 alkyl, halogen, acetyl, aldehyde, or hydroxyl.
10. The preparation of the palladium-supported carbon-based catalyst according to claim 8 and its application in the Suzuki coupling reaction, characterized in that, R2 is hydrogen, halogen, C1-C4 alkyl, C1-C4 alkoxy, halo-C1-C4 alkyl, or halo-C1-C4 alkoxy.
